Authentic Leadership and Human Resources Role for Future Work - Lucky Setiawan; Willson Gustiawan (Entrepreneurship and Small Business Research, 2023)
Authentic leadership is a style of leadership that emphasizes openness, sincerity, and honesty. Authentic leaders cultivate real relationships with their people by instilling trust and building a healthy work environment. Evaluating the publicly stated efforts of one world leader in terms of his ability to demonstrate his authentic leadership attributes during the COVID-19 pandemic response. Using existing literature, this article explores how his attitude has helped or hampered his leadership responsibilities. Furthermore, leadership is intimately tied to human resource management, particularly in terms of reacting to the future of work. The term "future of work" refers to a well-informed view of what companies and other organizations need to know about how work can change as a result of digitalization and other developments, as well as how workforces and workplaces should prepare for such changes. Organizations researching the post-COVID-19 future of work must customize their approach to their own circumstances. Therefore, this article also discuss the function of human resources in the workplace of the future.